Kolaborasi Guru Mata Pelajaran dan Guru BK Dalam Mengembangkan Karakter Siswa - Aena Nissa Fajri Awaliah; Nadiya Devinda; Naylla Fahhad; Sulastri Rizqi Apriliani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to systematically examine the form, role, challenges, and effectiveness of collaboration between subject teachers and guidance and counseling teachers in developing student character. Character education is an important part of the educational process because it relates not only to academic aspects, but also to the social, emotional, and moral aspects of students, thus requiring the integrated involvement of various parties in the school. This study uses a literature review method by examining relevant national journal articles obtained through online databases such as Google Scholar, GARUDA, and SINTA. The selected articles were analyzed based on their relevance to the focus of the study, particulary regarding collaboration patterns and their impact on student character development. The result of the study show that collaboration between subject teachers and guidance counselors plays an important role in strengthening student character, especially in terms of discipline, responsibility, religiosity, and social behavior. However, this collaboration still faces obstacles in the form of time constraints, differences in teachers perspectives, and the lack of a structured collaboration system. Therefore, institutional support is needed so that collaboration can run optimally and sustainably